ENVISION – Improve intensive care of COVID-19 patients with artificial intelligence - Värri, Alpo Olavi; Kallonen, Antti; Nieminen, Hannu; van Gils, Mark (Finnish Journal of eHealth and eWelfare, 2021)
The Envision project aims at developing artificial intelligence-based tools for supporting the treatment of critically ill COVID-19 patients in the intensive care unit. Twelve European hospitals participate in the collection of patient data for the development and validation of the artificial intelligence tools. Ten potential use cases have been identified as development targets. Data analysis and results from expert interviews are applied to define the clinically most relevant parameters and functional use cases to be used in providing decision support for the clinicians in the intensive care units for this patient group. The resulting artificial intelligence-based tool may be beneficial in the management of the next similar epidemics, as well.